Imagens de Nossa Senhora de Nazaré: iconografia, devoção e conservação - Idanise Sant'ana Azevedo Hamoy (2017)
In Belém do Pará, Brazil, the highlight of Catholic celebrations is the procession of the Círio de Nazaré, that is held in October, in the capital itself and in the other cities of the region, with the worship of Our Lady of Nazareth . Starting from issues that embraces historical studies, iconographic, anthropological and devotional, this thesis aims to investigate four images of Our Lady of Nazareth in Pará and the same time, to investigate its origin in the Shrine of Our Lady of Nazareth in Portugal. From the iconographic point of view we find a variety of representations which embraces several models that are represented through sculpture, painting and engraving, and had been spread in other regions of the Brazil. We also present the devotional meaning of these images which are an intrinsic part of the Feast of the Círio de Nazaré, which received the title of Intangible Heritage of Humanity by Unesco. Aiming the preservation of this sculptural collection, we also present several conservation protocols for these works which are between the material and immaterial and are part of the identity of the people of the Pará, preserving their materiality.